Analisis Pengendalian Persediaan Bahan Baku Pada Usaha Makanan Beku Dengan Menggunakan Metode EOQ (Economic Order Quantity) Studi Kasus Di Pt. Tanabe Food - Robbani, Syifa; Suparman, Suparman; Widyaningtyas, Shinta; Sam, Roisatun Nisa Firdausiyah Abdur Rouf; Ramadhani, Griselda Happy (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
One of the problems faced by business actors of PT Tanabe Food (Frozen Food) is the imbalance of good and proper raw material inventory. This study aims to analysis the raw material inventory process be adapted to the market's needs to minimize production costs and raw material inventory. This research uses the Economic Order Quantity (EOQ) method. Techniques in collecting data during this research are interviews, observation, and documentation. The results obtained in the research at PT Tanabe Food in using the EOQ method are the use of raw materials per period of 56,952.5 kg, the frequency of purchases is 12-13 times, the safety stock is 430.3 kg, the reorder point is 860.6 kg, and the total cost of raw material inventory is Rp. 5,356,168, while in the calculation, according to company policy is the use of raw materials per period of 61,964 kg, the frequency of purchases is 96 times, there is no safety stock, there are uncertain goods at the reorder point, and the total cost of raw material inventory is Rp. 87,281,408. The results show that the calculation of the EOQ method is more profitable than the company's existing calculations.